Pendidikan Kesehatan Terhadap Pengetahuan Ibu Dalam Penanganan Kegawatdaruratan Kejang Demam Pada Balita - Rahmat H. Djalil; Tezar Nusi; Frisilia C. Tangian (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Emergencies can occur if febrile seizures are not treated promptly. Trained mothers will be able to provide first aid to children. The purpose of this study was to determine the effect of health education using video media on mothers knowledge in handling febrile seizures emergencies in toddlers. This research using pre experimental designs. The sample was 16 respondents using accidental sampling technique. Data collection by distributing questionnaires, then processed using the McNemar statistical test with a significance level of α = 0.05. Before being given health education using video media 56.3% of respondents had poor knowledge after being given health education 87.5% of respondents had good knowledge. The McNemar test results obtained a p-value of 0.016, meaning that there is an effect of health education using video media on mothers knowledge.